15-Deoxy-Δ12, 14-prostaglandin J2 prevents oxidative injury by upregulating the expression of aldose reductase in vascular smooth muscle cells. (February 2014) - Kang, E. S.; Hwang, J. S.; Ham, S. A.; Park, M. H.; Kim, G. H.; Paek, K. S.; Yoo, T.; Lee, W. J.; Kang, K. R.; Lee, J. H.; Choi, Y. J.; Seo, H. G.
Abstract: The omega-6 fatty acid derivative 15-Deoxy-Δ 12, 14 -prostaglandin J2 (15d-PGJ2 ) is believed to play a role in cellular protection against oxidative stress in diverse cell systems. However, the cellular mechanisms by which protection is afforded by 15d-PGJ2 are not fully elucidated in vascular smooth muscle cells (VSMCs). In this study, we report the finding that 15d-PGJ2 elicited a time and concentration- dependent increase in aldose reductase (AR) expression. This induction was independent of the activation of peroxisome proliferator- activated receptor γ. Inhibition of phosphatidylinositol 3-kinase (PI3K) significantly suppressed the increase in expression and promoter activity of AR induced by 15d-PGJ2 . Luciferase reporter assays demonstrated that 15d-PGJ2 targets the multiple stress response regions comprising the antioxidant response element in the promoter of the AR gene. 15d-PGJ2 -mediated induction of AR promoter activity was potentiated in the presence of nuclear factor-erythroid 2-related factor 2 (Nrf2), but not in cells expressing dominant negative Nrf2. Cells treated with 15d-PGJ2 were resistant to oxidant-induced apoptotic cell death by inhibiting production of reactive oxygen species. These effects were significantly attenuated in the presence of an AR inhibitor or small interfering RNA against AR, indicating that AR plays a protective role against oxidative injury. Taken together, these findings demonstrate that activation of PI3K by 15d-PGJ2 increases the expression of AR through Nrf2, and increased AR activity may function as an important cellular response against oxidative injury.